Agent-based chemical mechanical planarization qualification for semiconductor wafer fabrication - Md Fauadi, Muhammad Hafidz Fazli; Ramlan, Samad; Razali, N.H.; Hao, X. (Penerbit Universiti Teknikal Malaysia Melaka, 2021)
Semiconductor wafer fabrication is one of the critical segments in overall integrated circuit (IC) production flow. There are number of processes involved in the wafer fabrication facility which are diffusion, ion implantation, lithography, etching and Chemical Mechanical Planarization (CMP). Process equipment is required to be in optimized condition. In order to achieve this, qualification is done on equipment prior to process production wafers. In CMP, qualification is to monitor pad performance. Pad performance depends on few critical parameters which are monitored by wafer thickness measurement. Measurement taken is based on Statistical Process Control (SPC) rules. Currently, the qualification activities are carried out manually based on Standard Operating Procedures (SOP) of wafer fab and Manufacturing Execution System (MES). For this purpose, agent based framework Is applied to enhance qualification activity. The measurement results are computed by agent to manage selected data points on the wafer and to derive specific parameters. The results show that the proposed method is capable to produce consistent results.